Relations between lower body isometric muscle force characteristics and start performance in elite male sprint swimmers - Beretic, I.; Durovic, M.; Okicic, T.; Dopsaj, M. (Journal of Sports Science & Medicine, 2013)
The aim of the present study was twofold. The first aim was to examine the influence of absolute and relative lower body muscle force on kinematic component which determine the start performance. The second aim was to create multiregressional model which could use as a tool for swimming coaches with the purpose to start performance control and improvement. Twenty seven high-level trained male competitive swimmers all members of the Serbian National Youth and Senior Swimming Team (Age = 21.1 ± 4.3 yrs., Height = 1. 89 ± 0.10 m, Weight = 81.6 ± 8.4 kg, 50m freestyle - long course = 24.36 ± 0.86 s) performed two trials of standing leg extensors isometric muscle force testing and three swimming start trials corresponding to 10m distance. The average start time significantly correlated with variables of leg extensors maximum voluntary force (Fmax, r = -0.559, p = 0.002), leg extensors relative muscle voluntary force (Frel, r = -0.727, p < 0.001), leg extensors specific rate of force development (RFD50%, r = -0.338, p = 0.047) and leg extensors relative value of specific rate of force development (RFD50%rel, r = -0.402, p = 0.040). Regression equation for t10m prediction was defined by following variables: maximum voluntary isometric force of leg extensors muscles at absolute and relative level (Fmax and Frel), as well as a specific rate of force development of the same muscle groups (RFD50% and RFD50%rel) at absolute and relative level too with 74.4% of explained variance. Contractile abilities indicators of the leg extensors muscles included consideration: Fmax, RFD50%, Frel and RFD50%rel showed significant correlation with swimming start times on 10m. Additionally, the results suggest that swimmers, who possess greater isometric maximum force and specific rate of force development at absolute and relative levels, tend to be able to swim faster on initial 10m swim start perforamnce.